Comparative pathology of dog and human prostate cancer. Issue 1 (10th October 2021) - Ryman‐Tubb, Toby; Lothion‐Roy, Jennifer H.; Metzler, Veronika M.; Harris, Anna E.; Robinson, Brian D.; Rizvanov, Albert A.; Jeyapalan, Jennie N.; James, Victoria H.; England, Gary; Rutland, Catrin S.; Persson, Jenny L.; Kenner, Lukas; et al.
Abstract: Though relatively rare in dogs, prostate cancer (PCa) is the most common non‐cutaneous cancer in men. Human and canine prostate glands share many functional, anatomical and physiological features. Due to these similarities, canine PCa has been proposed as a model for PCa in men. PCa is typically androgen‐dependent at diagnosis in men and for this reason, androgen deprivation therapies (ADT) are important treatments for advanced PCa in men. In contrast, there is some evidence that PCa is diagnosed more commonly in castrate dogs, at which point, limited therapeutic options are available. In men, a major limitation of current ADT is that progression to a lethal and incurable form of PCa, termed castrate‐resistant prostate cancer (CRPC), is common. There is, therefore, an urgent need for a better understanding of the mechanism of PCa initiation and progression to CRPC to enable the development of novel therapeutic approaches. This review focuses on the functional, physiological, endocrine and histopathological similarities and differences in the prostate gland of these species. In particular, we focus on common physiological roles for androgen signalling in the prostate of men and dogs, we review the short‐ and longer‐term effects of castration on PCa incidence and progression in the dog and relate how this knowledge may be relevant to understanding the mechanisms of CRPC in men. Abstract : Only three species, men, dogs and lions, are believed to develop prostate cancer. Here, we review the common and distinct features of prostate cancer in men and dogs, with a view to better understanding the disease in both species.